Novel complex medication containing medium chain triglycerides for the treatment of dry eye - T.N. Safonova; G.V. Zaytseva; K.Yu. Kravets; N.B. Polyakov (РМЖ "Клиническая офтальмология")
T.N. Safonova1, G.V. Zaytseva1, K.Yu. Kravets2, N.B. Polyakov3 1M.M. Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation 2V.I. Vernadskiy Institute of Geochemistry and Analytical Chemistry, Moscow, Russian Federation 3N.F. Gamaleya National Research Center of Epidemiology & Microbiology, Moscow, Russian Federation Background: the outer layer of the tear film is composed of nonpolar lipids, including free fatty acid esters, triglycerides (TG), and cholesterol esters. Alterations in their qualitative and quantitative composition can result in evaporative dry eye, which requires pathogenic treatment. Somatic comorbidities, particularly type 2 diabetes (T2D), may act as a potential etiological factor. Aim: to assess the efficacy of a new complex medication containing medium chain TGs for the treatment of dry eye. Patients and Methods: a single-center, observational, single-stage, controlled single-sample, non-randomized study was conducted. Twenty-seven patients (mean age 52.5±0.5 years) were included in the study. Group 1 included 12 patients with dry eye and T2D. Group 2 included 15 patients with dry eye but no T2D. Patients received a complex medication containing medium chain TGs and carbomer for one month. In addition to standard and additional eye examinations, tearscopy and low-resolution mass spectrometry using LCQ Fleet (Thermo Scientific, Germany) were performed. Results: a reduction in the levels of TG and cholesterol was demonstrated in both groups. The reduction was more significant in group 1. A complex medication containing medium chain TGs and carbomer for one month improved functional indices in group 1 patients compared with baseline (p <0.05). Corneal staining grade 1 was reported in 94% of group 1 patients. In group 2, corneal staining did not change significantly. Tearscopy revealed a significant improvement in the tear film lipid layer in group 1 (an increase in the lipid distribution coefficient and lipid thickness by 0.2 and 0.03, respectively) in comparison to group 2 (an increase by 0.1 and 0.02). Conclusions: decreased levels of TGs and cholesterol in T2D induce cellular dysfunction and inflammation in meibomian glands, thereby triggering dry eye development and/or worsening its course. In light of these considerations, complex medications containing TGs are necessary and reasonable. Keywords: medium chain triglycerides, carbomer, meibomian gland dysfunction, dry eye, mass spectrometry, diabetes. For citation: Safonova T.N., Zaytseva G.V., Kravets K.Yu., Polyakov N.B. Novel complex medication containing medium chain triglycerides for the treatment of dry eye. Russian Journal of Clinical Ophthalmology. 2024;24(2):64–68 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-4.